Board gender diversity and carbon emissions: European evidence on curvilinear relationships and critical mass - Claudio Nuber; Patrick Velte (Business Strategy and the Environment, 2021)
The role of European businesses in addressing environmental issues and climate change has taken center stage with the European Green Deal. With increasing attention to the effect of board gender diversity (BGD) on firms' environmental performance, the question arises whether BGD has any influence on carbon emissions. Based on legitimacy and critical mass theory, this study empirically investigates the impact of BGD on firms' carbon performance (CP), based on total carbon emissions intensity. The paper relies on two-stage least squares (2SLS) regressions with instrumental variable (IV) and a two-step generalized method of moments (GMM) system approach to analyze a cross-country sample of 3123 observations from non-financial firms in the European STOXX600 index over the 2009–2018 period. Our findings add to the growing empirical evidence twofold: (1) there is a robust linear and positive relationship between BGD and CP, whereas some indication of a U-shaped relationship is found; and (2) we find that a critical mass of at least two women directors needs to be reached to increase CP. Our research results contribute to the current discussion on sustainable corporate governance, especially in the European capital market, and have implications for researchers, business practice, and regulatory issues alike.
Keywords: 650; carbon emissions; carbon performance; climate change; corporate governance; critical mass; gender diversity